Learning Gaps due to COVID-19 among Middle School Students Indicated in Pandemic Era An Analysis - Chaurasiya, Deepika Pradeep; Singh, Sunita (JOURNAL OF INDIAN EDUCATION, 2023)
COVID-19 has had a significant influence on all aspects of global human existence. It has had a huge impact on the education sector, specifically in the developing countries. The purpose of this paper is to explore learning gap on students’ learning outcomes in subjects like English, Hindi and Maths due to the influence of the pandemic. The present paper is based on qualitative research design in which teachers, students and parents were interviewed and triangulation has been done through observation and focus group discussion. Study has been conducted from April 2022 (first week of school reopening after pandemic) to May 2022. Total 82 boys and girls of Class VI, VII and VIII were selected through purposive sampling and assessed to know the learning outcomes based on their reading ability of their own textbook, interpreting given picture text in writing, solving maths questions of their respective class related to operation of numerals, shapes, and geometrical understanding. Around 81 students, 10 teachers and f ive parents were also included as samples. Findings reveal that the majority of learners have been suffering from the problem of learning gaps due to lack of student-teacher interaction, access to resources, lack of attentive feedback to each individual learner and other equitable facilities. The Government has made significant efforts to respond to the effects of COVID-19, and the commitment is reflected in the various online platforms regarding dissemination of content of each school subject but perennial learning loss occurs in middle schools